EVALUASI PROGRAM LOYALITAS BERBASIS INSENTIF PADA OUTLET INDIHOME BY TELKOMSEL REGIONAL JABAR - Armilda, Raissa; Wijayanti, Reni; Taufik, Nur Imam; Ravenska, Nanda (GEMAH RIPAH: Jurnal Bisnis, 2025)
This study aims to evaluate the effectiveness of incentive-based loyalty programs in increasing outlet loyalty towards IndiHome by Telkomsel Regional Jabar. A descriptive qualitative approach was used, with data collected through in-depth interviews with the Household Operations team and selected outlets. The findings show that the program still faces several challenges, such as uneven reward distribution and lack of transparency in the points system. Nevertheless, it has succeeded in motivating active outlets and contributing to sales growth. This study provides strategic recommendations, including performance-based segmentation, transparency of point tracking, and the use of outlet feedback as a basis for developing future loyalty programs.